Livestock and fish value chain assessment toolkit - CGIAR Research Program on Livestock (2019)
The toolkit has been designed and piloted in the recent years, working with international (KIT Royal Tropical Institute, CIRAD Agricultural Research for Development) and national (Sokoine University of Agriculture, Tanzania Livestock Research Institute, Makerere University) research partners. The toolkit is available for use.